The Contributions of Fadama-II Project to the Socio-Economic and Infrastructural Development of Rural Communities in Ibarapa North Local Government Area (2011)
"The Fadama-Il part of the National Fadama Development Project was implemented to consolidate the gains of Fadama-I in Nigeria, in order to further improve the welfare of the rural people and enhance public participation in decision-making at the community level. This paper examines the contributions of Fadama-Il project to the socio-economic and infrastructural development Ibarapa North local government area of Oyo state. Nigeria. The paper presents the result of a questionnaire survey of Fadama User Groups (FUGs) carried out in 2009 in the study area. A total of 258 (20%) of the 1.290 members of 86 FUGs found in the three principal towns and twenty-two villages in the study area were sampled. Stratified and systematic random sampling techniques were used in the selection of sampled settlements and respondents respectively. Descriptive and inferential statistical methods were used for data analysis. Findings showed that the income of the rural poor improved significantly after partaking in the Fadama-Il projects with 56.6% of the respondents earning an average annual income of #200.000. 00 or more. There was also a drastic reduction in the proportion of people in low income class from 33.0% to 7.0%. The result of the paired samples t-test gave a t value of-4. 067at 257 degrees of freedom while the probability of occurring by chance is 0.000 which is lower at O.05 level of significance. The Fadama Community Associations (FCAs) provided about 33 rural infrastructural facilities. Based on its visible overall outcome. the paper argued that Fadama-Il project is a viable rural development and poverty alleviation strategy. It concluded that the project's goal of rural development was achieved in the study area and as such can be replicated in other rural communities in Oyo state and Nigeria. Recommendations are offered to sustain the success recorded by the project. "